Male involvement and maternal health outcomes: systematic review and meta-analysis - Yargawa, Judith; Leonardi-Bee, Jo (BMJ Publishing Group, 2015)
Background: The developing world accounts for 99% of global maternal deaths. Men in developing countries are the chief decision-makers, determining women's access to maternal health services and influencing their health outcomes. At present, it is unclear whether involving men in maternal health can improve maternal outcomes. This systematic review and meta-analysis aimed to investigate the impact of male involvement on maternal health outcomes of women in developing countries.